Impact of Procedural Simulation on Learning and Satisfaction of Tunisian Dental Students - Bekri, San; Mabrouk, Yosra; Labidi, Amel (The Indonesian Institute of Science and Technology Research, 2025)
The demand for quality and the growing ethical demand, as well as the fear of risk and its legal implications, now require a minimum acquisition of the gesture practice before its realization on the patient himself, by virtue of the founding ethical principle of teaching by simulation: